KABA GOMBANG PATUANAN DALAM PANDANGAN POSKOLONIAL - Eva Krisna (Pusbindiklat - LIPI, 2010)
Kaba Gombang Patuanan in the view of colonialism. This research discusses the representation of nativeresistance againts colonialism through life rature. This research used observation method and interpretation-understanding(verstehen-hermeneutic). In an occidental discourse, the superiority prominent of the colonized peopleto show that the colonizer is not the center of power.